Connecting Mobile Users Through Mobile Social Networks - Alkhateeb, Faisal; Manasrah, Ahmed M.; Abu Doush, Iyad; Al Maghayreh, Eslam (International Journal of Interactive Mobile Technologies (iJIM), 2012)
Nowadays, social networks become popular with the emerging of web-based social networking services. Recently, several mobile services are developed to connect users to their favourite social networks such as Facebook, Twitter, Flickr, etc. However, these services depends upon the existing web-based social networks. In this paper, we present a mobile service for joining groups across communities. The originality of the work is that the framework of the service allows creating and joining social networks that are self-contained for mobile company servers. The service consists of several sub-services such as users invitation, group finding and others. Users, regardless of their disability, can use the service and its sub-services without the need to create their own accounts on social web sites and thus their own groups. We also propose a privacy control policy for mobile social networks.